Relatório de Estágio Profissional "Da superação de expectativas à concretização de um sonho" - Alexandre Rafael Costa Almeida (2017)
The Professional Internship serves as the apex of academic education. It is therefore a milestone in my training as a physical education teacher. For one school year, the trainee teacher is confronted with the reality of trying to apply all of the knowledge gained. Accordingly, all the experiences during this year, among which a series of difficulties arose from the context in which the teaching practice was carried out are described. However, reporting of these experiences would not make sense if an eminently reflexive and critical character were not implicit. This is a key instrument and enhancer of learning that allows the beginning teacher to overcome this inexperience and improve his abilities, making him a competent teacher, a holder of a professional culture, able above all to teach and to be prepared to adapt to any context. The professional internship was held at a school in Porto, in a group of three trainee teachers, a cooperating teacher from the institution and a professor from the Faculty of Sport at the University of Porto. This document falls within the scope of the professional training course in the 2nd cycle of studies related to the Master's degree in Physical Education Teaching in Basic and Secondary Education and is composed of several chapters and sub-chapters. These possess a personal dimension, framing and implementation of professional practice, including design, planning, implementation and evaluation, participation in the school and relationship with the community, personal development, where a research study on the existence of retention of students' learning in the volleyball module was carried out after a didactic unit. Finally, a brief conclusion is presented, in which I reflect on the importance of the professional internship on my growth as a Physical Education Teacher as well as becoming an integral part of the entire educational community.